Bill Jacklin graphics - Lloyd, Jill; Campbell, Nancy (Royal Academy of Arts, 2015)
"This book brings together a comprehensive collection of prints by the New York-based British artist Bill Jacklin, from intimate early etchings and his seminal Anemones and Hong Kong suites, to the spectacular, gestural monotypes of his later career." -- Provided by publisher